PENGELOLAAN DANA DESA DALAM UPAYA MENINGKATKAN PEMBANGUNAN DI DESA BANYUATES KECAMATAN BANYUATES KABUPATEN SAMPANG - Moh Sofiyanto; Ronny Malavia Mardani; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT The purpose of this study is to know the management of Village Funds in an effort to increase the development and impact of the Village Fund on development in the village of Banyuates. Data analysis method used is quantitative descriptive analysis by using village head and village apparatus as informant. The results show that the Village Fund Management by Banyuates Village Government both technically and administratively has been run in accordance with existing regulations. The Village Government of Banyuates has been responsible for the management of the Village Fund well, this can be proved by the Letter of Accountability which consists of general cash book, receipts, letter of payment request, and memorandum of funds disbursement. In this case the village government is serious in managing the Village Fund to improve the facilities and infrastructure and the quality of Human Resources (HR) and Village Fund also give positive impact on development in Banyuates village both in the field of physical development and empowerment of society.Keywords: Management, Village Funds, Devolopment.